Investigation of failure mechanisms for gallium nitride (GaN) based high-electron-mobility transistors (HEMTs) - Hu, Shihao (Nanyang Technological University, 2023)
This study investigates the failure mechanisms of Gallium Nitride (GaN) based high-electron-mobility transistors (HEMTs) under high electric field through reverse bias stress condition. The report presents a detailed literature review of the basic theoretical backgrounds and known failure mechanisms associated with GaN HEMTs. Furthermore, the methodology used to assess GaN HEMTs, utilizing available standards and literature, is described. A group of AlGaN/GaN on Si HEMTs were subjected to electrical stress tests, and their degradation and failure were analyzed using various diagnostic techniques, including electrical measurements, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). The results show that the failure mechanisms of GaN HEMTs are complex. The failure modes identified were device breakdown, increased leakage current and current collapse degradation likely due to new trap center defect generation and leakage path under the gate. The study concludes with recommendations and conclusions related to the possible failure mechanisms identified during the investigation. This research aims to contribute to the advancement of GaN HEMT technology by providing valuable insights into their failure mechanisms and ways to improve their reliability and performance in various applications.